Nicotine-induced activation of caudate and anterior cingulate cortex in response to errors in schizophrenia. - Moran, Lauren V.; Stoeckel, Luke E.; Wang, Kristina; Caine, Carolyn E.; Villafuerte, Rosemond; Calderon, Vanessa; Baker, Justin T.; Ongur, Dost; Janes, Amy C.; Evins, A. Eden; Pizzagalli, Diego A. (Psychopharmacology, 2018)
Background Nicotine improves attention and processing speed in individuals with schizophrenia. Few studies have investigated the effects of nicotine on cognitive control. Prior functional magnetic resonance imaging (fMRI) research demonstrates blunted activation of dorsal anterior cingulate cortex (dACC) and rostral anterior cingulate cortex (rACC) in response to error and decreased post-error slowing in schizophrenia. Methods Participants with schizophrenia (n = 13) and healthy controls (n = 12) participated in a randomized, placebo-controlled, crossover study of the effects of transdermal nicotine on cognitive control. For each drug condition, participants underwent fMRI while performing the stop signal task where participants attempt to inhibit prepotent responses to "go (motor activation)" signals when an occasional "stop (motor inhibition)" signal appears. Error processing was evaluated by comparing "stop error" trials (failed response inhibition) to "go" trials. Resting-state fMRI data were collected prior to the task. Results Participants with schizophrenia had increased nicotine-induced activation of right caudate in response to errors compared to controls (DRUG × GROUP effect: pcorrected < 0.05). Both groups had significant nicotine-induced activation of dACC and rACC in response to errors. Using right caudate activation to errors as a seed for resting-state functional connectivity analysis, relative to controls, participants with schizophrenia had significantly decreased connectivity between the right caudate and dACC/bilateral dorsolateral prefrontal cortices. Conclusions In sum, we replicated prior findings of decreased post-error slowing in schizophrenia and found that nicotine was associated with more adaptive (i.e., increased) post-error reaction time (RT). This proof-of-concept pilot study suggests a role for nicotinic agents in targeting cognitive control deficits in schizophrenia.